Bump cap - Rosaidi, Najwa Qisteena; Ridha, Irsalina Nadia Shah; Othman, Siti Amira (Penerbit UTHM, 2020)
Industrial hazard are situations faced by industrial workers which may lead to minor or major injuries. Being struck by a brick at a construction site, falling from a roof 20 feet above the ground, bumping their head on a wall or even a stepping on random nails scattering on the ground, these are all the unexpected events that anybody on the working sites might encounter when they are working. Some of these accidents cause non-fatal injuries while the rest cause fatal injuries. Out of all the injuries involved, Traumatic Brain Injuries (TBI) is one of the causes of death that often happens in the case of industrial death. It often happens when a big impact is given to parts of the head which lead to injuries to the brain and other complications including death. Other than these fatal injuries, other minor injuries could also happen such as bumping or laceration on the head and these injuries should not be taken lightly as we never know if these small injuries might cause bigger problems to the victims’ safety and health. Since TBI is one of the serious injuries that often occurs when an industrial accidents happen, head protection is very important and suitable safety headgears are required for the workers to ensure their safety while working.